Comparison of Red-Complex Bacteria Between Saliva and Subgingival Plaque of Periodontitis Patients: A Systematic Review and Meta-Analysis - Jiang, Yaling; Song, Bingqing; Brandt, Bernd W.; Cheng, Lei; Zhou, Xuedong; Exterkate, Rob A. M.; Crielaard, Wim; Deng, Dong Mei (Frontiers in Cellular and Infection Microbiology, 2021)
The development of periodontitis is associated with an imbalanced subgingival microbial community enriched with species such as the traditionally classified red-complex bacteria (Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola). Saliva has been suggested as an alternative to subgingival plaque for the microbial analysis due to its easy and non-invasive collection. This systematic review aims to determine whether the levels of red-complex bacteria assessed using saliva reflect those in subgingival plaque from periodontitis patients. The MEDLINE, EMBASE, and Cochrane Library databases were searched up to April 30, 2021. Studies were considered eligible if microbial data of at least one of the red-complex species were reported in both saliva and subgingival plaque from periodontitis patients, based on DNA-based methods. Of the 17 included studies, 4 studies used 16S rRNA gene sequencing techniques, and the rest used PCR-based approaches. The detection frequency of each red-complex species in periodontitis patients was reported to be > 60% in most studies, irrespective of samples types. Meta-analyses revealed that both detection frequencies and relative abundances of red-complex bacteria in saliva were significantly lower than those in subgingival plaque. Moreover, the relative abundances of all 3 bacterial species in saliva showed significantly positive correlation with those in subgingival plaque. In conclusion, current evidence suggests that one-time saliva sampling cannot replace subgingival plaque for microbial analysis of the red-complex bacteria in periodontitis patients. Given the positive microbial associations between saliva and subgingival plaque, a thorough review of longitudinal clinical studies is needed to further assess the role of saliva.